Divine words, female voices: Muslima explorations in comparative feminist theology - Rhodes, Jerusha Tanner (Oxford University Press, 2018)
Interreligious feminist engagement is a legitimate and vital resource for Muslim women scholars seeking to articulate egalitarian interpretations of Islamic traditions and practices. Acknowledging very real challenges within interreligious feminist engagement, 'Divine Words, Female Voices' uses the method of comparative feminist theology to skillfully navigate these challenges, avoid impositions of absolute similarity, and propose new, constructive insights in Muslima theology